PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) DI RS TENTARA PEMATANGSIANTAR TAHUN 2023 - Sri Suci Rahayu Barus (Jurnal Inovasi Kesehatan Masyarakat, 2023)
In implementing SMK3 in a hospital, there are several SMK3 criteria consisting of OSH Policy Determination, OSH Planning, OSH Plan Implementation, OSH Performance Monitoring and Evaluation, and OSH Performance Review and Improvement. The approach used in this study is a mixed method. Mixed methods research design with the design used in this research is the exploratory sequential design. This research was conducted at the Pematang Siantar Army Hospital. The time for the research was from November 2022 to May 2023. The research informants consisted of 5 people, namely the Main Informants: Director of the Hospital, K3 Staff, Head of HR and K3 Committee. Triangulation informants: 1 infection prevention and control team (PPI). The OHS Management System that has been implemented at the Pematang Siantar Army Hospital based on the Regulation of the Minister of Health of the Republic of Indonesia No. 52 of 2018, namely the preparation of a K3 implementation decree, the preparation of written K3 plan documents in the form of an annual work plan, waste management, monthly reporting of work accident rates and disease rates work and the implementation of occupational health services and emergency response and which are not yet perfect at the Siantar Army Hospital, namely the unavailability of Antam's technical personnel. It is necessary to form an OHS team in accordance with the standards of the Minister of Health of the Republic of Indonesia No. 52 of 2018, carry out continuous training related to Hospital OHS for all employees at the Hospital, create a well-programmed B3 waste management program, so that the Hospital no longer uses 3rd parties and waste can be managed independently, making a commitment to make the implementation of K3 a priority program at the Pematang Siantar Army Hospital.